The features of international and national standards in the management of innovative projects - Yessengeldin, B.S.; Sitenko, D.A.; Abildina, M.K. (Вестник Карагандинского университета, 2016)
The article deals with the characteristics of innovative projects. The paper considers the criteria for selecting innovative projects by the state bodies of the Republic of Kazakhstan: innovation, competitiveness, scale. Article determinates the mechanisms and conditions for financing of industrial and innovative projects: loans, bridge financing, mezzanine financing and project financing. Project management standards of the United Kingdom, Japan, the United States and the Republic of Kazakhstan are studied.
Keywords: project; innovative project; project management; standard; project financing